Single nucleotide polymorphism of adiponectin +276 G/T is associated with the susceptibility to essential hypertension in a Turkish population. (16th November 2016) - Demir, Ayşe Kevser; Kaya, Süheyla Uzun; Şahin, Şafak; Benli, İsmail; Bütün, İlknur; Erken, Ertuğrul; Tasliyurt, Turker
ABSTRACT: Background : It is well known that arterial stiffness is associated with hypertension. Recent studies have shown that adiponectin +276 G/T, ACE I/D, AGTR1 A1166C, and eNOS E298D polymorphisms are likely to be risk factors for arterial stiffness. In this study, we aimed to investigate possible associations between these single-nucleotide polymorphisms (SNPs) and essential hypertension in a Turkish population. Methods : The study population consisted of 170 patients who were diagnosed with essential hypertension and 170 sex- and age-matched controls. Genotyping of adiponectin +276 G/T, ACE I/D, AGTR1 A1166C, and eNOS E298D SNPs were performed using real-time polymerase chain reaction and commercially produced kits. Results : The percentage of the adiponectin +276 T allele carriers was significantly higher in the patients with hypertension (33%) than in the controls (25%, p < 0.011). Through multiple logistic regression analysis, the adiponectin +276 T allele carrier was found to be associated with an increased risk of hypertension (TT vs. GG and TG: odds ratio = 3.318, p = 0.014, 95% confidence interval: 1.269–8.678). The genotype distributions or allelic frequencies of ACE I/D, AGTR1 A1166C, and eNOS E298D SNPs did not significantly differ between the patients with hypertension and the controls. Conclusion : The present study demonstrated that the adiponectin +276 G/T SNP is likely to be a risk factor for essential hypertension in a Turkish population.